BEHAVIOR MODIFICATION PROGRAM TO PREVENT DIABETES AND HYPERTENSION OF THE STAFF AT RISK IN HIGHER EDUCATION INSTITUTIONS - Pradubkaew, Sutapat; Sarayutpitak, Jintana; Kritpet, Thanomwong (Academic Journal of Thailand National Sports University, 2020)
The purpose of this research was to develop a behavior modification program to prevent diabetes and hypertension of staff at risk in higher education institutions. Documentary research and related comprehensive articles were analyzed and synthesized, Health belief model and health literacy were used. After the program was developed, the content of the program and the consistency of the content was presented to five experts for assesment including 1) assessment form for content validity, activity components, 2) content validity evaluation of 10 activities, and 3) an evaluation form for content validity of the developed program. The results showed that index of congruence of the program consisted of title of the program, activities. purpose, conceptual framework, steps in the activities was 1.00. This program had 10 activities, i.e., 1) Build up Friendship to Promote Positive Power 2) Hope 3) Holistic Health 4) Self-review 5) Right on the Target 6) Yoga for Relax 7) Let’s relax 8) Nutrition Knowledge 9) My Favorite Menu 10) My Idol. The average mean of index of congruence was 0.88. It was suggested the program should be 8 weeks, 3 days a week, 1 hour per day. The index of congruencies of the overall program was 0.87. The program was determined to promote the staff at risk to modify their behavior.